1995
DOI: 10.1063/1.115330
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature photoluminescence of erbium-doped hydrogenated amorphous silicon

Abstract: A comparison of the photoluminescence of Er-doped hydrogenated amorphous silicon and crystalline silicon a-Si:H(Er) and c-Si(Er), is presented. It is shown that a-Si:H(Er) exhibits efficient room-temperature photoluminescence at 1.537 μm which is as strong as the emission from optimized c-Si(Er) at 2 K. Most remarkably, there is practically no temperature quenching of the emission intensity in the range 2–300 K. The experiments suggest that the lifetime connected with the Er-induced emission is considerably sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
4

Year Published

2000
2000
2007
2007

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 107 publications
(35 citation statements)
references
References 6 publications
1
29
0
4
Order By: Relevance
“…For Er-doped c-Si, the high excitation cross-section s exc ($10 À15 cm 2 ) of Er is strongly thwarted by a strong temperature quenching of the Er photoluminescence (PL) induced by energy back-transfer and Auger processes [2][3][4]. This PL temperature quenching is much weaker for Er-doped a-Si [5], but at the expense of an emission lifetime of only tens of microseconds [6]. In contrast, Er-doped SO offers the double advantage of good thermal stability of Er PL and an emission lifetime as high as 11 ms, but suffers from a low s exc ($10 À20 cm 2 ) [7].…”
Section: Introductionmentioning
confidence: 98%
“…For Er-doped c-Si, the high excitation cross-section s exc ($10 À15 cm 2 ) of Er is strongly thwarted by a strong temperature quenching of the Er photoluminescence (PL) induced by energy back-transfer and Auger processes [2][3][4]. This PL temperature quenching is much weaker for Er-doped a-Si [5], but at the expense of an emission lifetime of only tens of microseconds [6]. In contrast, Er-doped SO offers the double advantage of good thermal stability of Er PL and an emission lifetime as high as 11 ms, but suffers from a low s exc ($10 À20 cm 2 ) [7].…”
Section: Introductionmentioning
confidence: 98%
“…One of the widely used approaches for the solution of this problem is doping of silicon with erbium, which in an intra-ion radiative transition emits light of 1.5 µm wavelength, corresponding to minimum losses in fiber-optics transmission lines. As an alternative to erbium-doped crystalline silicon, characterized by fairly strong quenching of erbium luminescence with rise of temperature, amorphous silicon was proposed as a promising matrix with a larger bandgap [2,3].…”
mentioning
confidence: 99%
“…It has been suggested that the strong thermal quenching of photoluminescence in c-Si(Er) arises from the thermally induced depopulation of the Er-induced impurity donor state, which presumably is located 15-170 meV below the conduction band edge. Within this interpretation the relative weak temperature dependence in a-Si:H<Er> suggest that the Er-related level is positioned deeper in the forbidden gap in a-Si:H that in c-Si(Er) [1]. In our previous work [7] we have clearly shown that the structure of the a-Si:H film is affected when erbium is incorporated onto the host matrix.…”
Section: Wavelength (Nm)mentioning
confidence: 88%
“…The use of an amorphous matrix allows to surmount these problems. This is the reason why several research teams are studying the erbium doping of a-Si:H [1][2][3]. Hydrogenated amorphous silicon is a promising host material to obtain intense Er 3+ emission due to its large modulable bandgap [4].…”
Section: Introductionmentioning
confidence: 99%